SMALL BUSINESS AND PRIVATE ENTERPRISES: CATALYSTS FOR ECONOMIC GROWTH (Journal of Science-Innovative Research in Uzbekistan, 2024)
Small businesses and private entrepreneurs play an important role in economic growth, supporting innovation and creating employment opportunities. The article examines the importance of small business and private entrepreneurship in terms of economic development. It examines the challenges these entities face and strategies to support their growth and sustainability. Based on empirical evidence and case studies, this article emphasizes the contribution of small businesses and private entrepreneurs to the economy and the importance of creating an enabling environment for their success. Small businesses and private enterprises play a critical role in driving economic growth, supporting innovation and creating jobs around the world. It discusses the main features of small business and private entrepreneurship, their role in promoting economic development and strategies to support their growth. It also studies the impact of small businesses and private enterprise on innovation, job creation and poverty reduction. At the end of the article, the importance of creating a favorable environment for the development of smallbusiness and private entrepreneurship entities is emphasized